Assessing cognitive impairment in home-dwelling Chinese elders aged 80+: a detailed survey of 13,000 participants focusing on demographic factors, social engagement, and disease prevalence - Bian, Sensen; Tian, Xiaobing; Meng, Fanli; Xu, Chunjie; Zhao, Yan; Gao, Qian; Bian, Chengzhi (Frontiers in Psychiatry, 2024)
Introduction: Cognitive Impairment (CI) in the elderly, encompassing conditions ranging from Mild Cognitive Impairment (MCI) to dementia, represents a growing public health concern globally. This study aims to investigate the prevalence and correlates of CI among individuals aged 80 and above.Methods: The study conducts 13,027 elderly individual's door-to-door surveys, followed by the cross-tabulation of analysis data, logistic regression analysis, and health condition assessments to examine various determinants of CI.Results: The current study's key findings demonstrate sub-statical correlations between CI and various factors, including educational attainment, marital status, and gender. Pronounced differences are evident between urban and rural demographics. Furthermore, aspects of social engagement, notably communication proficiency and sensory capabilities, exhibit a strong association with CI. Logistic regression analysis highlights that residing in rural areas (Odds Ratio [OR] = 0.637) and being female (OR = 0.71) are linked to a decreased risk of CI. In contrast, behavioral and healthrelated variables present a complex picture. Specifically, aggressive behavior (Adjusted OR = 1.881) and symptoms of depression (Adjusted OR = 0.549) contrast with conditions such as asthma (OR= 2.857) and cerebral infarction (OR=1.348), which elevate the risk of CI. Intriguingly, hyperlipidemia (OR= 0.671) appears to confer a protective effect against CI.The study highlights the complexity of factors affecting CI in the elderly, advocating for a comprehensive approach to understanding and managing cognitive health.